Long Distance Transport and Welfare of Farm Animals - Appleby, MC (CABI, 2014)
This book is a review of the effects of long-distance transport for slaughter on the welfare of farm animals, of its occurrence and variation worldwide and of ways in which problems for both animals and people may be addressed. It brings together authoritative views and experiences from 28 authors from 18 countries, all of them drawing from international sources and many drawing directly from an initial, even wider resource of contributors.